Penyuluhan Gizi Seimbang Pada Anak Usia Sekolah di UPT SDN 145 Gresik - Ayu, Friska; Afina, Rizka Dany; Raudhatul Jannah, Ken Putri; Sofia, Ainin; Adani, Tarissa Shinta; Cahyawati, Nindy Kurnia; Riskiani, Aprillia; Rahmawati, Vidia; Larasati, Diah Ayu; Mulyani, Mulyani; Alfiah, Anggi (Lembaga Dongan Dosen, 2024)
Balanced nutrition education for school-age children is a crucial effort to enhance understanding and awareness of the importance of healthy eating habits that support optimal growth and development. This study aims to evaluate the impact of balanced nutrition education conducted at UPT SDN 145 Gresik on students' knowledge and eating habits. The method used was direct conseling with an interactive approach involving 82 students from grades 5 to 6. The materials presented include the concepts of